Deformation kinetics of pH-sensitive hydrogels - Toh, William (2014)
Polymeric gels can undergo large deformation when subjected to external solutions of varying pH. It is imperative to understand the deformation process of pH-sensitive hydrogels for the effective application of these attractive materials in the biomedical and microfluidic fields. In the modeling of these multi-phase materials, finite element (FE) modeling is a useful tool for the development of future applications, and it allows developers to test a wide variety of material responses in a cost-effective and efficient manner, reducing the need to conduct extensive laboratory experiments. Although a FE user-defined material model is available for the equilibrium state, the transient response of pH-sensitive gels has not been effectively modeled. Based on our recent work using the heat transfer analogy to tap into the readily available coupled temperature–displacement elements available in the commercial FE software ABAQUS for simulation of the transient swelling process of neutral hydrogels, the transient swelling process of a pH-sensitive hydrogel is studied and a FE model is further developed to simulate the transient phenomena. Some benchmark examples are investigated to demonstrate the model's capabilities in the simulation of nonlinear deformation kinetics relevant to several applications of pH-sensitive hydrogels.